Faktor Yang Berhubungan Dengan Work Life Balance Pada Perawat Wanita Yang Sudah Menikah Di Ruang Rawat Inap Rumah Sakit Khusus Daerah (RSKD) Dadi Sulawesi Selatan (Window of Public Health Journal, 2025)
Work-life balance is a state of equilibrium between work and life, where a person is equally committed to both work responsibilities and family or personal life responsibilities. Work-life balance is an important factor for every nurse, ensuring that nurses maintain a balanced quality in their relationships with their families and achieve a balance in their work. This study aims to determine factors related to work-life balance in married female nurses in the inpatient ward of the Dadi Regional Special Hospital (RSKD) in South Sulawesi Province. This study used a quantitative research method with an observational analytical design and a cross-sectional study approach. The sampling technique used in this study employed a total sampling approach, where all members of the population were included, specifically 68 nurses. Data analysis employed both univariate and bivariate analyses, utilizing the chi-square test. This research instrument used a questionnaire. According to the results of the chi-square test, there is a relationship between workload and work life balance, namely (p = 0.000